Uplifting Blockchain Technology for Data Provenance in Supply Chain - Martin Parmar, Dr. Parth Shah (International Journal of Advanced Science and Technology, 2020)
A supply chain is a crucial part of many business industries that flows the goods and services to end-users. The services include different processes such as choosing the right raw materials, forming end products, and deliver to the target users through different intermediaries. The industry needs to keep track of every single information during each product transfer phase with complete product visibility in the network.  Todays’ supply chain process demands to keep information synchronized properly with all the participants in a transparent manner without any violation of data integrity. The system must ensure strong authenticity, confidentiality, and integrity to all the participants of the network. The records need to be verified by all the participating peers and stored securely in a distributed manner to achieve complete data provenance. However, information traceability becomes a cumbersome process for the current manufacturing industry as well as for the agriculture food processing industry. Blockchain technology fulfills an important gap by providing clear ownership of assets, transparency, traceability, and limit human errors. This paper gives the potential of Blockchain for supply chain, available platforms to implement decentralized applications, evaluation matrix for Blockchain, and discuss known issues of Blockchain.Keywords: Blockchain Technology, Supply Chain, Food Supply Chain, Data Provenance, Performance Matrix.